The Effect of Team Games Tournament (TGT) in Social Science Learning to Improve Student Learning Outcomes - Jenny Koce Matitaputty; Nugroho Susanto; Muhammad Rijal Fadli; Iwan Ramadhan; Christofer Judy Manuputty (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
Abstract The Team Games Tournament (TGT) method is effective for improving student learning outcomes in social science learning, but there are still very few teachers who apply this method. The TGT method creates a competitive and collaborative learning environment where students engage in group games to deepen their understanding of social science concepts and develop social skills. This study aimed to investigate the TGT in social science learning to improve student learning outcomes. This study used a quasi-experimental with two experimental and control classes. The population used was fifth-grade elementary school students in Lampung, and the number of samples was 133. The sampling technique used cluster random sampling in determining the sampling, while the data collection was in the form of a questionnaire instrument. Questionnaires were analyzed using the n-gain score and Kruskal-Wallis tests to determine whether there was an increase in historical research skills with the help of SPSS 25. The results showed that the influence of the TGT in social science learning significantly improved student learning outcomes. The TGT method uses a competitive and collaborative group play approach to create an interesting and motivating learning environment for students. By applying the TGT, students become more involved and enthusiastic in social science learning. They actively participate in group play that involves discussion, teamwork, and joint problem-solving.Keywords: learning methods, teams games tournament (TGT), social science,      learning outcomes.AbstrakMetode Team Games Tournament (TGT) merupakan metode efektif untuk meningkatkan hasil belajar siswa dalam pembelajaran IPS, namun masih minim guru yang menerapkan metode ini. Metode TGT digunakan untuk menciptakan lingkungan pembelajaran yang kompetitif dan kolaboratif, di mana siswa terlibat dalam permainan kelompok untuk memperdalam pemahaman konsep IPS dan mengembangkan keterampilan sosial. Tujuan penelitian ini adalah untuk menginvestigasi TGT dalam pembelajaran IPS untuk meningkatkan hasil belajar siswa. Penelitian ini menggunakan quasi eksperimen dengan dua kelas eksperimen dan control. Populasi yang digunakan siswa kelas V sekolah dasar di Lampung dan jumlah sampel 133. Teknik sampling menggunakan cluster random sampling dalam menentukan sampling, sedangkan pengumpulan data berupa instrument angket. Angket dianalisis menggunakan uji n-gain score dan Kruskal-Wallis untuk mengetahui adanya peningkatan pada keterampilan meneliti sejarah dengan bantuan SPSS 25. Hasil penelitian menunjukkan bahwa pengaruh TGT dalam pembelajaran IPS memiliki dampak yang signifikan dalam meningkatkan hasil belajar siswa. Metode TGT menggunakan pendekatan permainan kelompok yang kompetitif dan kolaboratif untuk menciptakan lingkungan pembelajaran yang menarik dan memotivasi siswa. Dengan menerapkan TGT, siswa menjadi lebih terlibat dan antusias dalam pembelajaran IPS. Mereka berpartisipasi aktif dalam permainan kelompok yang melibatkan diskusi, kerja tim, dan pemecahan masalah bersama.Keywords: metode pembelajaran, teams games tournament (TGT), IPS,       hasil belajar.